1993
DOI: 10.1111/j.1574-6968.1993.tb06544.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bacillus thuringiensis strain which is toxic to the housefly Musca domestica

Abstract: A Bacillus thuringiensis isolate has been discovered which is toxic to the common housefly (Musca domestica) as well as other Diptera and Lepidoptera. Crystal δ‐endotoxins purified from this isolate killed 50% of Musca larvae at a concentration of 10.2 μg/ml, and β‐exotoxin was not detected. Sodium dodecyl polyacrylamide gel electrophoresis of the purified crystals revealed three protein species which were related to CryIA(b), CryIB and CryIIA toxins on the basis of immunoreactivity and amino‐terminal sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…When challenged with specific cry1 primers only, they produced six different profiles which were identical to those of standard strains as follows (Table 3) New toxic specificities may stem from new combinations of known genes, such as in the strains displaying profiles 9 and 10. For example, B. thuringiensis YBT-226 (14) produces Cry1Ab and Cry1Ba (toxic to Lepidoptera) as well as Cry2Aa (toxic to both Lepidoptera and Diptera). This strain is highly toxic to the common housefly, Musca domestica, despite the fact that the toxicity of Cry2Aa is low (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When challenged with specific cry1 primers only, they produced six different profiles which were identical to those of standard strains as follows (Table 3) New toxic specificities may stem from new combinations of known genes, such as in the strains displaying profiles 9 and 10. For example, B. thuringiensis YBT-226 (14) produces Cry1Ab and Cry1Ba (toxic to Lepidoptera) as well as Cry2Aa (toxic to both Lepidoptera and Diptera). This strain is highly toxic to the common housefly, Musca domestica, despite the fact that the toxicity of Cry2Aa is low (14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, B. thuringiensis YBT-226 (14) produces Cry1Ab and Cry1Ba (toxic to Lepidoptera) as well as Cry2Aa (toxic to both Lepidoptera and Diptera). This strain is highly toxic to the common housefly, Musca domestica, despite the fact that the toxicity of Cry2Aa is low (14). Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers (e.g., Johnson et al, 1998; Hodgman et al, 1993; McGaughey and Johnson, 1987) have identified numerous isolates of Bacillus thuringiensis as being toxic to house flies. Several experiments were conducted to determine if a biological agent was the cause of the toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…6). Many lepidopteran species are sensitive to Cry1A, and dipteran A. aegypti and M. domestica are also sensitive to Cry1Ab but not to Cry3A (Hodgman, 1993; van Frankenhuyzen, 2009; Bravo et al ., 2013; Melo et al ., 2016). Cry3A is specific to coleopteran species such as T. castaneum , Anoplophora glabripennis and L. decemlineata (van Frankenhuyzen, 2009; Melo et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%